2013
DOI: 10.1177/0741713613504125
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of National Culture on Informal Learning in the Workplace

Abstract: The purpose of this article was to identify how differing cultural factors affect informal learning in the workplace. We have introduced concepts and reviewed studies on informal learning and national culture based on an extensive literature review on the factors influencing informal learning, particularly based on five Hofstede’s dimensions of national culture. Findings suggest that adult education and workplace learning professionals need to attend to cultural influences and efforts at indigenization when fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 66 publications
(113 reference statements)
2
49
0
2
Order By: Relevance
“…The variation among students in their readiness for SDL might be because of individual demographical differences, which might affect their educational goals, motivation to learn, attitudes towards teaching and teachers, and responses to the classroom and clinical practice environments. Such factors could affect their readiness for SDL as well as their dominant styles of learning (Felder and Brent, 2005;Kim & McLean 2014). Similarly, according to Yuan et al (2012) the increased level of SDLR might indicate increased emphasis on self-responsibility and relative independence in clinical practice, thereby helping students to rehearse adult roles and prepare them for the beginning of their nursing careers.…”
Section: Discussionmentioning
confidence: 99%
“…The variation among students in their readiness for SDL might be because of individual demographical differences, which might affect their educational goals, motivation to learn, attitudes towards teaching and teachers, and responses to the classroom and clinical practice environments. Such factors could affect their readiness for SDL as well as their dominant styles of learning (Felder and Brent, 2005;Kim & McLean 2014). Similarly, according to Yuan et al (2012) the increased level of SDLR might indicate increased emphasis on self-responsibility and relative independence in clinical practice, thereby helping students to rehearse adult roles and prepare them for the beginning of their nursing careers.…”
Section: Discussionmentioning
confidence: 99%
“…14 This collective socialisation, manifested in words, thoughts and actions, distinguishes the members of one culture from another. [15][16][17][18] In terms of a country's culture, whilst acknowledging within-country differences, there is often strong homogeneity in terms of values amongst members. Further, rather than possessing a unique set of values, different countries demonstrate a complex range of scores (or loading) across similar value clusters.…”
Section: National Cultural Valuesmentioning
confidence: 99%
“…Culture can be defined as a set of attitudes, beliefs, values and self‐definitions shared by a community . This collective socialisation, manifested in words, thoughts and actions, distinguishes the members of one culture from another . In terms of a country's culture, whilst acknowledging within‐country differences, there is often strong homogeneity in terms of values amongst members.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Rothwell (2003) found that only less than 30 percent of what people learn in formal learning activities that are actually transferred to job in a way that improves work performance. This means that formal learning activities are no longer sufficient for continuous learning at the workplace (Billett, & Choy, 2013;Kim, & McLean, 2014;Marsick, 2009). Thus, the focus of professional development has shifted from formal to informal learning activities in recent years (Billett, & Choy, 2013;Marsick,2009).…”
Section: Introductionmentioning
confidence: 99%